Evidence of Anaplasma phagocytophilum and Borrelia burgdorferi infection in cats after exposure to wild-caught adult Ixodes scapularis. (July 2015) - Lappin, Michael R.; Chandrashekar, Ramaswamy; Stillman, Brett; Liu, Jiayou; Mather, Thomas N.
Cats are infected by Anaplasma phagocytophilum and Borrelia burgdorferi when exposed to infected Ixodes scapularis (black-legged ticks). The purpose of our study was to allow wild-caught I. scapularis to feed on healthy research cats ( n = 4) and temporally evaluate for A. phagocytophilum DNA in blood by a polymerase chain reaction (PCR) assay as well as for antibody responses to the B. burgdorferi C6 peptide, to the A. phagocytophilum P44 peptide, and to a novel A. phagocytophilum peptide (P44-4). Prior to I. scapularis infestation, all cats were negative for antibodies against both organisms based on a kit optimized for dog serum, and negative for A. phagocytophilum DNA in blood using a conventional PCR assay. Using the pre-infestation samples, an enzyme-linked immunosorbent assay for detecting antibodies against the P44-4 peptide was optimized. Cats were infested with wild-caught I. scapularis for 7 days. Genomic DNA of A. phagocytophilum was amplified from the blood before antibodies were detected in all 4 cats. Antibodies against the C6 peptide, P44 peptide, and P44-4 peptide were detected in the sera of all 4 cats. Antibodies against P44-4 were detected prior to those against P44 in 3 out of 4 cats. The results suggest that a PCR assay should be considered in acutely ill cats with suspected anaplasmosis that are seronegative.